Pengaruh Penerapan Anggaran Berbasis Kinerja Terhadap Akuntabilitas Kinerja Instansi Pemerintah - Nana Marliyana; Jouzar Farouq Ishak; Hastuti (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
Performance Responsibility of Government Corporation is essential because it’s stated in legal basis or organizational rules, which are required to fulfill their orgainzatonal accountability with the performance stipulated in the performance-based budget. This study points to decide the impact of actualizing performance-based financial by focusing on transparancy and accountability on the performnce accountability of government agencies in West Bandung Regency SKPD. This study uses quantitative studies methods with a survey technique. The sample used in observe were 28 Regional Work Units (SKPD) in West Bandung Regency. The quantity of respondents in this observe were 53 people. In this observe, Microsoft Excel and SPSS were assisted to analyze the data. The information analysis method used on this studies is multiple linear regression. Based on the check, it is known that transparency and responsibility impact the execution responsibility of government offices in West Bandung Regency, with a large effect of 68.1%.